Radiation and Contrast Medium Dosage Optimization of Coronary CT Angiography While Combining Personalized Patient Protocol Technology and Automated Tube Voltage Selection Technology - Jingkun Sun; Yang Zhou; Ge Zhang; Lijun Zhang; Xinnan Shen; Zhiwei Zhang (Diagnostics, 2026)
Objective: This study aims to investigate whether combining automated tube voltage selection (ATVS) with P3T for contrast injection in coronary computed tomography angiography (CCTA) allows for patient-tailored scanning protocols. Specifically, we assessed whether this combination maintains equivalent image quality and adequate diagnostic image quality. Methods: This retrospective study included 378 patients who underwent CCTA using ATVS and P3T technologies. We divided the patients into three groups based on the scanning tube voltage: 70-, 80-, and 90-kV groups. Furthermore, each group was divided into sequence and spiral scanning subgroups based on the acquisition method. The CM injection volume and rate, volume CT dose index (CTDIvol), and dose–length product (DLP) were recorded. The CT value of the enhanced coronary artery, noise, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR) were calculated by artery segment. Image quality was evaluated using a four-point grading scale in a double-blind manner. Results: The SNR did not differ among the groups in any segments (p > 0.05). And the subjective image quality showed only minor differences among the groups. The body weight, which determines ATVS and P3T protocol algorithm, is positively correlated with the automatic tube voltage, CM injection volume, and effective radiation dose. Furthermore, when using the same tube voltage under the combined ATVS and P3T protocols, sequence scanning yielded a lower radiation dose than spiral scanning (p < 0.05). Conclusions: CCTA combining ATVS and P3T technology enables individualized scanning protocols while maintaining adequate diagnostic image quality.